Ecologies of faith in a digital age : spiritual growth through online education - Lowe, Stephen D., 1949-; Lowe, Mary Ella (Downers Grove, Illinois : InterVarsity Press, 2018)
Technological innovation has changed nearly everything about human life, including how we teach and learn. Many Christian professors and institutions have embraced new technologies, especially online education. But as followers of Jesus Christ, we face the same call to grow in our faith. So how should we think about and approach Christian education in light of new technologies? Is it possible for us to grow spiritually through our digital communities? Steve Lowe and Mary Lowe, longtime proponents of online education, trace the motif of spiritual growth through Scripture and consider how students and professors alike might foster digital ecologies in which spiritual growth -- even transformation -- can take place.
Part 1. A biblical theology of ecology. God's garden ecology -- The ecological motif in scripture -- The ecological power of parables -- The ecology of the body of Christ -- Part 2. Spiritual formation through digital ecologies. Growing together online -- Designing learning ecologies -- Digital ecologies across the digital landscape -- Social networks and the power of reciprocal influence -- Part 3. Ecological connections to Christ and community. Ecological connection to Christ -- Ecological connections to Christians -- Ecological interactions with other Christians -- Ecological sanctification -- Thinking ecologically about spiritual growth.
Includes bibliographical references and index.
Keywords: Spiritual formation; Christian education; Education -- Effect of technological innovations on; Internet in education